Judgment at Appomattox - Peters, Ralph, 1952- (Forge, 2020)
A great war nears its end. Robert E. Lee makes a desperate, dramatic gamble. It fails. Ulysses S. Grant moves. Veteran armies clash around Petersburg, Virginia, as Grant seeks to surround Lee and Lee makes a skillful withdrawal in the night. Richmond falls. Each day brings new combat and more casualties, as Lee's exhausted, hungry troops race to preserve the Confederacy. But Grant does not intend to let Lee escape ... In one of the most thrilling episodes in American history, heroes North and South, John Brown Gordon and Phillip Sheridan, James Longstreet and Francis Channing Barlow, battle each other across southern Virginia as the armies converge on a sleepy country courthouse.